Molecular Detection of Mycoplasma pneumoniae in Adults with Community-Acquired Pneumonia Requiring Hospitalization - Dorigo-Zetsma, J. Wendelien (American Society for Microbiology, 2001)
Mycoplasma pneumoniae infection was diagnosed in 18 (12.5%) of 144 adults hospitalized with community-acquired pneumonia. The infection was demonstrated by PCR in 15 patients and by serology, using two methods, in 10 patients. The mean age of the 8 patients with positive M. pneumoniae PCR and negative serology was significantly higher than that of the 10 patients with positive serology.